EFFECTIVE USE OF MODERN TECHNOLOGY IN THE DEVELOPMENT OF PEDAGOGY - Turdiyeva Shakhidakhon Anvardjanovna (Galaxy International Interdisciplinary Research Journal, 2024)
The advancement of modern pedagogical technologies has had a profound impact on the field of pedagogy, transforming traditional teaching methods and creating exciting new possibilities for educators and learners alike. This article explores the role of these technologies in facilitating the development of the science of pedagogy. It discusses the benefits, challenges, and future prospects of integrating technology into educational practices, showcasing the potential to enhance learning outcomes, adapt instruction to diverse learner needs, and foster innovation in pedagogical research and practice.